Grace in Christian Religious Tradition - Chethimattam, John B (Journal of Dharma, 1987)
Divine Grace may be said to be the most fundamental religious concept of the Christian tradition. For the Judeo-Christian strand of religion faith is not an ontology of God for man nor its final goal a dissolution and dis- appearance of the INDIVIDUAL in the transcendent and all embracing reality of the ABSOLUTE. Instead it is more an anthropology of man before God, the meaning of divine graciousness and generosity for the life of human beings. Religious history is salvation history, history of the great deeds of God showing concern and compassion for all his children. Grace is charis, a free gift, agracious self-communication from God to the human self, rendering it pleasing and acceptable and raising it to a divine level of existence. Such a concept has full relevance only in the context of a God- man interpersonal relationship on which the whole Christian religion is built up. In this paper I shall briefly examine the Judaic background of the Christian concept of Grace, its evolution in the New Testament literature, later development along with other points of Christian faith, and the con- temporary issues that bear on Christian life 3S a life of grace.